2015
DOI: 10.1063/1.4909545
|View full text |Cite
|
Sign up to set email alerts
|

Complex permittivity characterization of serum with an air-bridge enhanced capacitor for quantifiable detection of glucose

Abstract: We proposed the complex permittivity characterization of serum sample on an air-bridge enhanced capacitor for the mediator-free glucose sensor in the radio frequency of 7.37 GHz. An air-bridge enhanced capacitor with integrated passive device process on a gallium arsenide substrate was implemented for the design, fabrication, and testing to enable effective quantifiable detection of glucose levels in human serum. The decomposition parameters such as complex permittivity, air-bridge capacitance, phase and corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The post-fabrication process involved wire-bonding the device to the printed circuit board (PCB) for safe measurement and handling. The realized IPD-based sensor was shown to be an appropriate candidate for the sensitive detection of the water-ethanol concentration, inheriting the functionality of previously proposed IPD-based glucose sensors such as reusable, robust, and mediator-free operation [ 3 , 16 , 20 ].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The post-fabrication process involved wire-bonding the device to the printed circuit board (PCB) for safe measurement and handling. The realized IPD-based sensor was shown to be an appropriate candidate for the sensitive detection of the water-ethanol concentration, inheriting the functionality of previously proposed IPD-based glucose sensors such as reusable, robust, and mediator-free operation [ 3 , 16 , 20 ].…”
Section: Methodsmentioning
confidence: 98%
“…Various methodologies, such as (complementary) split-ring resonators [ 5 , 12 , 13 ] and interdigital capacitors [ 14 , 15 ], have been adopted for the characterization of biomolecules in the microwave region. In our previous work [ 16 ], we developed an air-bridge capacitor-based microsensor realized through integrated passive device (IPD) technology for the effective characterization of the complex permittivity of human serum.…”
Section: Introductionmentioning
confidence: 99%
“…GaAs substrates have become the second most important semiconductor materials owing to their high saturated electron drift velocity, low field mobility, low parasitics, and good interdevice isolation. Thus, they can be employed in various systems, including medical treatment, information storage, communications, military application, lasing, and sensing [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, conventional sensitivity in glucose sensing has size issues, whereas metamaterial-inspired sensors can be miniature. Another research group [16] reported air-bridge enhanced capacitor-based glucose detection using complex permittivity characterization. They have also extracted all parameters form the measured S-parameter.…”
Section: Introductionmentioning
confidence: 99%